Industrialisation for employment and growth in India : lessons from small firm clusters and beyond - Nagaraj, R. (Cambridge : Cambridge University Press, 2021)
India initiated liberal economic reforms in 1991 to transform a slow-growing, state-led economy into an open, export-oriented industrialising economy. Though economic growth has accelerated, industrialisation has suffered from the manufacturing sector's share and labour intensive sectors failing to improve in India's exports. The government launched the Make in India initiative in 2015 aimed at raising the manufacturing sector's share in GDP to 25 percent, and to create an additional 100 million jobs by 2022. Though official estimates show an optimistic image of small scale industries, they do not explain why India failed to boost industrial production as expected of the reforms. Why did they fail to keep the domestic market, let alone expand exports? What would it take to meet the ambitious policy goals of the initiative? This book attempts to address these questions. It looks at a series of case studies of the small industry to obtain an in-depth understanding of specific industries and locations to draw meaningful conclusions.
Title from publisher's bibliographic system (viewed on 30 Jul 2021).
Keywords: Industrialization -- India; Economic development -- India; Employment (Economic theory) -- India; Labor market -- India; Industrial policy -- India